Asymmetric supercapacitors by integrating high content Na+/K+-inserted MnO2 nanosheets and layered Ti3C2Tx paper. (1st February 2020) - Chen, Si; Zhang, Mingyi; Ma, Xinzhi; Li, Lu; Zhou, Xuejiao; Zhang, Zhenyi
Abstract: In this work, Na + /K + - inserted MnO2 (Nax Ky MnO2 ) nanosheets are synthesized on Ni foam via a facile and efficient route based on an electro-deposition and electro-oxidation reaction process. The Nax Ky MnO2 nanosheet arrays has a broad potential window, which can be extended to 1.0 V versus standard calomel electrode (vs. SCE). The Nax Ky MnO2 with iso-oriented feature and unique nanoarchitectures provides shortened diffusion path lengths for both Na +, K + and electronic transport, and reduces the stress associated with Na +, K + insertion and extraction. The layered Ti3 C2 Tx paper on Ni foam (Ti3 C2 Tx @NF) are also synthesized successfully that can act as a negative electrode, stably in a negative potential window of −0.8−0 V (vs. SCE). Subsequently, an aqueous asymmetric supercapacitor is demonstrated with a high potential of 1.8–2.0 V by using Nax Ky MnO2 @NF as the positive electrode and Ti3 C2 Tx @NF as the negative electrode. The asymmetric device achieves a high power density of 9.396 mW/cm 2 and improved energy density of 0.11 mWh/cm 2, as well as great cycling performance.